2008
DOI: 10.1002/app.29005
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis of polyamide 6/MWNTs nanocomposites by anionic ring opening polymerization

Abstract: In situ anionic ring opening polymerization is used to prepare monomer casting polyamide 6 (MCPA6)/carbon nanotubes (CNTs) nanocomposites, whereby water is used as auxiliary dispersing agent of hydroxyl functionalized multiwalled carbon nanotubes (MWNTs-OH) and e-caprolactam (CL) monomer. The MWNTs-OH were dispersed homogenously in MCPA6 matrix when being observed through transmission electron microcopy. The well dispersed MWNTs-OH existed at the center of many radial texture phases in MCPA6 matrix. Polarizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Radial textures with black spots at their centers were homogeneously dispersed in the MCPA6 matrix, as shown in Figure 4(a). These radial textures were attributed to the spherulitic morphology of MCPA6 crystals, which had been confirmed by us 29. Figure 4(b) showed that the black spots were well dispersed MWNTs.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Radial textures with black spots at their centers were homogeneously dispersed in the MCPA6 matrix, as shown in Figure 4(a). These radial textures were attributed to the spherulitic morphology of MCPA6 crystals, which had been confirmed by us 29. Figure 4(b) showed that the black spots were well dispersed MWNTs.…”
Section: Resultssupporting
confidence: 74%
“…MWNTs did not exhibit large weight loss until 550°C. Comparatively, for MWNTs‐NCO and MWNTs‐PA6, major decomposition took place at a temperature that ranged from 200 to 500°C corresponding to the surface grown TDI and PA6 28, 29. If the mass loss of the MWNT‐OH at 550°C is used as the reference, the amount of TDI and PA6 covalently attached to MWNTs determined by TGA is about 8.0 and 21.5 wt %, respectively, as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Figure 5, the thermal decomposition of neat nylon 6 and its composite materials with different untreated and treated TiO 2 loadings is characterized by presence of two DTG peaks, indicating that there exist two stages of weight loss T max1 and T max2 , respectively. It is seen from Figure 5 that the first step ( T max1 ) is most evident on the derivative curve and can be probably attributed to the fact that a few of unreacted ε‐caprolactam monomer or oligomers which still remained in the neat nylon 6 and nylon 6 matrix due to strong hydrogen bonding between ε‐caprolactam and nylon 6 induce the decomposition of polymer at a lower temperature, under nitrogen atmosphere [39, 40] . The second step arises from the decomposition of neat nylon 6 and nylon 6 matrix [39, 40].…”
Section: Resultsmentioning
confidence: 99%
“…It is seen from Figure 5 that the first step ( T max1 ) is most evident on the derivative curve and can be probably attributed to the fact that a few of unreacted ε‐caprolactam monomer or oligomers which still remained in the neat nylon 6 and nylon 6 matrix due to strong hydrogen bonding between ε‐caprolactam and nylon 6 induce the decomposition of polymer at a lower temperature, under nitrogen atmosphere [39, 40] . The second step arises from the decomposition of neat nylon 6 and nylon 6 matrix [39, 40]. With increasing the concentration of untreated TiO 2 particles the T peak2 of the nylon 6 composites decreases very slightly, while in case surface‐treated TiO 2 particles T peak2 of the nylon 6 composites slightly increases.…”
Section: Resultsmentioning
confidence: 99%